Prevalence of Risk Factors for Dementia in Elderly Population in a Tribal Area of Central India – A Community-Based Cross-Sectional Study - P Kaushik Ragubathy; Hemant Adikane (Journal of Medical Sciences and Health, 2020)
Background: Approximately 50 million people worldwide are suffering from dementia, it is the 7th leading cause of death among the elderly. In India, more than 4 million people have some form of dementia 3. According to the World Health Organization, India’s population of those aged over 65, which was 40 million in 1997, is set to increase to 108 million by 2025 and 240 million by 2050. Aim and Objective: The aim of the study was to study the prevalence of risk factors of dementia among the elderly population residing in a tribal area of Central India. Materials and Methods: A door to door cross-sectional study was conducted in the rural/tribal area with a pre-designed case record form that investigated the prevalence of risk factors along with measurement of anthropometry and mini-mental state examination was used to categorize subjects according to their mental status. Results: This study reports high prevalence of risk factors such as hypertension (31.8%), tobacco chewing (25.43%), high waist-hip ratio (24.57%), smoking habit (15.03%), head injury (11%), overweight (9.54%), alcohol intake (9.25%), 71–80 age (9.25%), diabetics (9%), stroke (4.62%), family history of dementia (2.6%), obesity (2.31%), coronary artery disease (CAD) (1.73%), and depression (1.45%). Conclusions: This study highlights a significant burden of undiagnosed cases of hypertension, diabetes, depression, and CAD all of which are important risk factors for dementia in the community, most of them are poorly controlled. There is a need to identify the large pool of undiagnosed cases of the mentioned morbidities by screening and offer early treatment to avoid complications.